The efficiency of detecting the failures and troubleshooting while applying technical diagnostics for multi-computer systems - Ye, K.Z. (Institute of Automatic Control - Silesian University of Technology, 2015)
This paper presents techniques which base on the concept of flows thinning together with the identification techniques. These methods are proposed to determine the expected number of failures to assess the efficiency of technical diagnostics of instruments. Additionally, this research focuses on the improvement of multi-machine troubleshooting systems, based on the 'AND-OR' graphs. Respective algorithms are presented. The majority principle uses the input information to check the correctness of the decision regarding identification of faulty machines. In this paper we base on the complete testing algorithm for elements of multi-computer complexes searching by criteria of failed element. Â© 2015 Archives of Control Sciences.